FORMULASI TABLET EKSTRAK KANGKUNG AIR (Ipomoea aquatica F.) DENGAN VARIASI KADAR AMILUM MANIHOT SEBAGAI BAHAN PENGHANCUR - Sutrisna Khaidir; Mimiek Murrukmihadi; Aris Perdana Kusuma (Universitas Islam Indonesia, 2015)
Ipomoea aquatica F. are plant that has a hypoglycemic effect. Ipomoea aquatica F. was formulated into tablet dosage forms to produce benefits in terms of practicality and accuracy of therapeutic doses.Disintegrant has effect to release the active substance rate of the tablet so that drug effects can be felt by patients with diabetic immediatly. The purpose of this study was to determine disintegration time of Ipomoea aquatica F. extract tablets with various levels of amilum manihot and determine the best concentration of amilum manihot based on the evaluation of physical properties of tablets.Ipomoea aquatica F. extracts was obtained from the maceration using 96% ethanol, than concentrated by rotary evaporator. The extracts were tested qualitatively by TLC with petroleum eter: aceton: dietil amin mobile phase (10:4:1), the phase silica gel F254 with Rf value about 0,625. Tablets were formulated with amilum manihot concentration variation of 10%, 15% and 20% by wet granulation method. Physical properties of granules were tested such as powder flow, angle of repose, porosity and compressibility index.Tablets were tested to know physical properties such as weight uniformity, sizeuniformity, hardness, friability and disintegration time.The results showed that variaton levels of amilum manihot decrease disintegration time. Variation of amilum manihot was affected in disintegration time, and the optimumt formula with was achieved by 15% amilum manihot.